Suspicious minds? Empirical analysis of insider witness assessments at the ICTY, ICTR and ICC - Chlevickaitė, Gabrielė (European journal of criminology, 2023)
The testimonies of insider witnesses are often key to prosecutions of international crimes, despite significant trustworthiness concerns. However, we know little about the practice of judicial assessments of insider testimonies, that is, which factors the judges consider relevant to relying on insider testimony. With this article, we set out to provide a comprehensive, explorative examination of the insider witness assessment factors used by the trial judges at the International Criminal Tribunal for the former Yugoslavia, the International Criminal Tribunal for Rwanda and the International Criminal Court in 1996?2019. By using multiple correspondence analysis, we show that the factors related to insider witness assessment outcomes are generally similar across the tribunals and tend to focus on the contents of the testimonies, with less attention given to credibility or competence concerns. This research constitutes the first systematic quantitative analysis and cross-institutional comparison of insider witness assessment practice at an international level.